Respuesta :
Answer:
x = 46 ft
Step-by-step explanation:
We use the Angle Bisector Theorem to help solve this.
When we draw out the triangle, we should see that our angle bisector theorem would equal to:
[tex]\frac{63.8}{58} =\frac{55}{x+4}[/tex]
We then cross multiply and solve for x:
63.8(x + 4) = 55(58)
63.8x + 255.2 = 3190
63.8x = 2934.8
x = 46
Answer: x = 46 ft
Step-by-step explanation:
We use the Angle Bisector Theorem to help solve this.
When we draw out the triangle, we should see that our angle bisector theorem would equal to:
We then cross multiply and solve for x:
63.8(x + 4) = 55(58)
63.8x + 255.2 = 3190
63.8x = 2934.8
x = 46
Step-by-step explanation: